Report on proposed upgrading interior works for Coliseum Cafe and hotel at Lot 98 -100,Jalan Tunku Abdul Rahman,Kuala Lumpur / Amir Azfar Hamzah - Hamzah, Amir Azfar (Faculty of Architecture, Planning and Surveying, 2010)
This Diploma level Interior Design final project is towards student understanding about the interior design project’s whole aspect that had been studied from the basic level until the design proposal presentation. The selected final project is a proposed upgrading of Coliseum Cafe and Hotel at Jalan Tunku Abdul Rahman, Kuala Lumpur. With the outcome of a heritage institution and information source from client, Mrs. Chong Yoke Kek, it is hoped to make our heritage institution get more appreciation because always keep the responsibilities in concerning and care about national history and precious belonging treasures. The concept and image is also apply to both interior and exterior to appeal the cafe and hotel will be able to lure more tourists and visitors who were always keen in our aesthetic values in architecture. There were several researchers analyzed to succeed this cafe and hotel final project, among them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the client, Mrs. Chong Yoke Kek demands in terms of function and aesthetic value.